Analysis of three polymorphisms in Bidayuh ethnic of Sarawak population: a report from Malaysia - Vasudevan, Ramachandran; C. P. N., Fathihah; Ismail, Patimah (Academic Journals, 2011)
Insertion/deletion polymorphism of YAP (DYS287), M96 and M120 polymorphisms in Bidayuh ethnic populations of Sarawak, Malaysia were analyzed in this study. Genomic DNA was extracted from 180 buccal samples and amplified by Hot-Start PCR method. The amplified PCR products were separated by using 2% agarose gel electrophoresis. 26 out of 180 samples (14.44%) have shown insertion (YAP+) polymorphism, while the rest of the samples (85.56%) have shown deletion (YAP-) polymorphism. M96 derived and ancestral allele reveal 102 (56.67%) and 78 (43.33%), respectively and 96 (53.33%), while for M120 derived allele and 84 (46.67%) for M120 ancestral allele. This study has provided the information about the distribution of YAP, M96 and M120 polymorphisms in Bidayuh ethnic population of Sarawak. This study has to be continued with more samples to determine the YAP polymorphism and also the biallelic markers in Bidayuh population.